Elucidating the mechanism of stigmasterol in acute pancreatitis treatment: insights from network pharmacology and in vitro/in vivo experiments - Zhao, Xuanlin; Li, Fan; Wen, Ao; Yu, Xiuxian; Xu, Xinrui; Wan, Chengyu; Cao, Yu; Xin, Guang; Huang, Wen (Frontiers in Pharmacology, 2024)
IntroductionAcute pancreatitis (AP) is a severe inflammatory disease of the pancreas that could trigger a systemic inflammation and multi-organ dysfunction. Stigmasterol, a natural plant sterol found in various herbs and vegetables, exhibits a significant anti-inflammatory, antioxidant, and cholesterol-lowering effects. However, its therapeutic potential in AP have not been thoroughly investigated.MethodsThe present study employed network pharmacology combined with experimental verification to explore the protective effect of stigmasterol on AP and its molecular mechanism in a sodium taurocholate (STC)-induced AP mouse model.ResultsProtein-protein interaction (PPI) analysis pinpointed out MAPK3, also named as ERK1, as a promising stigmasterol target in AP therapy. Molecular docking analysis further revealed a strong binding capacity of stigmasterol to ERK1 (−6.57 kL/mol). Furthermore, both in vivo and in vitro studies demonstrated that stigmasterol treatment notably attenuated STC-induced pancreatic injury, as evidented by decreased serum levels of lipase and amylase, improved systemic inflammation, and reduced acinar cell necrosis. At the molecular level, stigmasterol treatment exhibited a significant inhibition on STC-induced activation of ERK signaling pathway in pancreatic acinar cells, leading to the transition of acinar cell death from necrosis to apoptosis, thereby preventing acinar cell necrosis-induced systemic inflammation.ConclusionThis study demonstrated that stigmasterol exhibits a significant protective effect aganist AP, at least in part through enhancing acinar cell apoptosis via modulating the ERK signaling pathways.